Abdominal obesity: Prevalence,sociodemographic and lifestyle-associated factors in adolescents - Tebar, William R. [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; Scarabotollo, Catarina C. [UNESP]; Zanuto, Edner F. [UNESP]; Saraiva, Bruna T.C. [UNESP]; Tebar, Fernanda C.S.G. [UNESP]; Delfino, Leandro D. [UNESP]; Christofaro, Diego G.D. [UNESP] (Faculdade de Filosofia e Ciências, 2017)
Introduction: Among human development stages, adolescence comprises the period in which intense somatic and behavioural changes occur1. In this period of life, the presence of detrimental health habits can be consolidated until and into adulthood, and can be a precursor for higher risk of mortality and chronic diseases. Objective: The aim of this study was to determine the prevalence of abdominal obesity and its associated factors among adolescents, independent of confounders. Methods: A sample of 14-17-year-old individuals (n = 1.231), who were students from Londrina/PR - Brazil public schools, was studied. A questionnaire about physical activity, sedentary behaviour and socioeconomic conditions was applied. Anthropometry was composed of body weight (kg), height (m), body mass index (BMI = kg/m2) and waist circumference (cm). The association of abdominal obesity and independent variables was assessed using the chi-square test and the magnitude of associations was verified using Binary Logistic Regression in an unadjusted model and adjusted for confounders (gender, age, socioeconomic status, physical activity and sedentary behaviour). The confidence interval and statistical significance were set at 95% and 5%, respectively, using SPSS v15.0. Results: The abdominal obesity prevalence was 17.5% (CI = 15.4%-19.6%), and was higher in boys than in girls. Adolescents with abdominal obesity had higher values of body weight, height, body mass index and sedentary behaviour compared to eutrophic individuals. Being male increased the risk of abdominal obesity by 36% in adolescents. This risk was two times higher in those with high levels of sedentary behaviour. Conclusion: Abdominal obesity was significantly associated with gender and high levels of sedentary behaviour, regardless of confounding factors. Lifestyle habits are important modifiable risk factors that can effectively contribute to the reduction of obesity from an early age.
Keywords: Abdominal obesity; Adolescents; Sedentary behaviour; Waist circumference